Neuronal DNA damage response‐associated dysregulation of signalling pathways and cholesterol metabolism at the earliest stages of Alzheimer‐type pathology. (7th July 2015) - Simpson, Julie E.; Ince, Paul G.; Minett, Thais; Matthews, Fiona E.; Heath, Paul R.; Shaw, Pamela J.; Goodall, Emily; Garwood, Claire J.; Ratcliffe, Laura E.; Brayne, Carol; Rattray, Magnus; Wharton, Stephen B.; et al.
Abstract : Aims: Oxidative damage and an associated DNA damage response (DDR) are evident in mild cognitive impairment and early Alzheimer's disease, suggesting that neuronal dysfunction resulting from oxidative DNA damage may account for some of the cognitive impairment not fully explained by Alzheimer‐type pathology. Methods: Frontal cortex (Braak stage 0–II) was obtained from the Medical Research Council's Cognitive Function and Ageing Study cohort. Neurones were isolated from eight cases (four high and four low DDR) by laser capture microdissection and changes in the transcriptome identified by microarray analysis. Results: Two thousand three hundred seventy‐eight genes were significantly differentially expressed (1690 up‐regulated, 688 down‐regulated, P  < 0.001) in cases with a high neuronal DDR. Functional grouping identified dysregulation of cholesterol biosynthesis, insulin and Wnt signalling, and up‐regulation of glycogen synthase kinase 3β. Candidate genes were validated by quantitative real‐time polymerase chain reaction. Cerebrospinal fluid levels of 24(S)‐hydroxycholesterol associated with neuronal DDR across all Braak stages ( r s  = 0.30, P  = 0.03). Conclusions: A persistent neuronal DDR may result in increased cholesterol biosynthesis, impaired insulin and Wnt signalling, and increased GSK3β, thereby contributing to neuronal dysfunction independent of Alzheimer‐type pathology in the ageing brain. Abstract : Dysregulation of cholesterol biosynthesis, impaired insulin and Wnt signalling and increased GSK3β are associated with the neuronal DNA damage response and are implicated in age‐related neuronal dysfunction independent of Alzheimer pathology.